1998
DOI: 10.1002/(sici)1521-186x(1998)19:2<131::aid-bem13>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Increased dexamethasone-induced apoptosis of thymocytes from mice exposed to long-term extremely low frequency magnetic fields

Abstract: To address the effect of extremely low frequency electromagnetic fields on programmed cell death we assessed both the spontaneous and dexamethasone (Dex)‐induced apoptosis of thymocytes and spleen cells from mice submitted to a long‐term continuous exposure of a 0.4–1.0 μT 60 Hz magnetic field or an 8–20 μT direct current (DC) magnetic field. Dex‐induced apoptosis but not spontaneous apoptosis was substantially increased in thymocytes from 0.4 to 1.0 μT 60 Hz field‐exposed animals. Spontaneous apoptosis and De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…Recent studies investigating changes in susceptibility to apoptosis with regard to EMF exposure have reported both decreased [Fanelli et al, 1999] and increased susceptibility [Flipo et al, 1998;Ismael et al, 1998]. Interestingly, previous studies involving DNA repair and EMF exposure have reported no effect [Cossarizza et al, 1989a;Frazier et al, 1990;Cantoni et al, 1995Cantoni et al, , 1996.…”
Section: Introductionsupporting
confidence: 68%
“…Recent studies investigating changes in susceptibility to apoptosis with regard to EMF exposure have reported both decreased [Fanelli et al, 1999] and increased susceptibility [Flipo et al, 1998;Ismael et al, 1998]. Interestingly, previous studies involving DNA repair and EMF exposure have reported no effect [Cossarizza et al, 1989a;Frazier et al, 1990;Cantoni et al, 1995Cantoni et al, , 1996.…”
Section: Introductionsupporting
confidence: 68%
“…Both hydroxy radical and nitric oxide have been shown to cause apoptotic and necrotic cell death, especially in brain cells (Simonian and Coyle 1996). In addition to the present study, others have shown apoptosis in various other cell types after exposure to extremely lowfrequency electromagnetic fields (Blumenthal et al 1997;Ismael et al 1998;Phillips et al 1997;Simko et al 1998;Singh et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the effects of exposure to ELF magnetic fields on previously induced apoptosis have also been investigated, but the results are inconsistent. The observations are as follows: (1) an increase of dexamethasone-induced apoptosis of thymocytes from mice exposed to long-term ELF magnetic field (Ismael et al 1998); (2) a transient suppression of X-ray-induced apoptosis by exposure to power frequency magnetic fields in MCF-7 cells (Ding et al 2001); and (3) protection from heatinduced apoptosis mediated by magnetic fields in HL-60, HL-6R and Raji cells (Robison et al 2002).…”
Section: Introductionmentioning
confidence: 99%